Consumer Perceptions and SWOT Analysis of Seed Products From the Seed Center Teaching Factory - Harlianingtyas, Irma; Pratiwi, Berlina Yudha; Kusuma, Satria Indra (International Journal of Technology, Food and Agriculture, 2024)
Superior rice seeds can increase production by at least 10%/ha, but this program must be supported by the availability of seeds, and easy access to seeds at affordable prices for farmers. One of the superior seed producers in Jember is the Seed Center Teaching Factory of Politeknik Negeri Jember. Seed Center products are distributed to areas around Jember, Bondowoso, Situbondo, Probolinggo, and several areas outside Java. Sustainable products are affected by product quality and maintaining customer satisfaction. This research aims to analyze consumer perceptions, measure customer satisfaction, and determine recommendations for product improvements and marketing strategies that appropriate consumer needs. Data were collected through interviews and questionnaires while using SWOT analysis.  The sample in this study included agricultural shops as regular consumers and farmers as direct users. The results show that all seed products are in great demand by consumers and farmers, namely Inpari 32, Logawa, Ceherang, and Sintanur. The biggest weakness is limited buyer partners, products not always available, and outlets far from the market. Besides that, the biggest opportunity is an abundant market and basic needs products supported by the government. The strength is that the products are complete business legality and certified seeds, affordable prices, solid team, and sufficient business capital.